Anti-Atopic Dermatitis Effect of Seaweed Fulvescens Extract via Inhibiting the STAT1 Pathway - Tae-Young Gil; Yun-Mi Kang; Ye-Jin Eom; Chul-Hee Hong; Hyo-Jin An (Hindawi Limited, 2019)
Seaweed fulvescens (SF) is a green alga rich in chlorophyll with unique flavor and taste. It is also called Maesaengi which has antioxidant and other physiological activities. In the present study, we evaluated the therapeutic effects of SF in a mouse model of Dermatophagoides farinae body-induced atopic dermatitis (AD) and in tumor necrosis factor-α and interferon-γ-stimulated HaCaT keratinocytes. SF treatment (200 mg/mouse) inhibited the development of AD symptoms, compared to that in the control group, as evidenced from the improved dorsal skin lesion, reduced thickness and infiltration of inflammatory cells and smaller lymph nodes, and reduced levels of proinflammatory cytokines. In HaCaT keratinocytes, SF (10, 25, and 50 μg/mL) suppressed the production of proinflammatory cytokines in a dose-dependent manner. In addition, SF reduced the phosphorylation of signal transducer and activator of transcription 1, which is one of the major signaling molecules involved in cellular inflammation. These results suggested that SF could be a potential therapeutic alternative for the treatment of AD.